PENINGKATAN KEMAMPUAN BERHITUNG MELALUI PERMAINAN ULAR TANGGA PADA ANAK KELAS B DI TK BUKIT PERMAI 2 DI DESA KAMPILI KABUPATEN GOWA - Fatimah Usman; Sukmawati; Sri Sufliati Romba (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The main problem in this study is how to improve children's numeracy skills through snakes and ladders games in class B at Bukit Permai 2 Kindergarten in Kampili Village, Gowa Regency. This type of research is classroom action research consisting of implementation planning, observation and reflection. The research subjects were 1 teacher and 17 children in class B at Bukit Permai 2 Kindergarten. The object of this study was the ability to recognize number symbols through a game of snakes and ladders. Data collection techniques used observation and documentation. The instruments used were observation sheets and documentation results. Data analysis used is descriptive quantitative. The results of this study indicate that there is an increase in numeracy skills in class B children at Bukit Permai 2 Kindergarten. The research implementation in cycle I and cycle II showed that children's numeracy skills could be seen from the percentage of observations of children's numeracy abilities in cycle I was 39.7% and the percentage of observations on the ability to recognize children's number symbols in cycle II was 82.8% with very good development criteria. Thus it can be concluded that using the snake and ladder game can improve the ability to recognize number symbols in class B children at Bukit Permai 2 Kindergarten.